Development, Validation and Statistical Correlation of RP–LC Methods for Determination of Atazanavir Sulfate in Capsule Dosage Form - A. Behera; D. G. Sankar; S. K. Moitra; S. C. Si (E-Journal of Chemistry)
To study the effective therapeutic bioavailability of Atazanavir Sulfate (ATV), administered singly or in combination with Ritonavir, a cost effective and rapid method is required. In order to assess an in-depth study, it is primarily thought prudent to develop an effective analytical method for estimation of ATV in marketed dosage forms. The present work is to develop a simple and precise analytical method for in depth evaluation of therapeutic efficacy of ATV. The novelty of the method shows linearity in the concentration range of 10-100 µg/mL at two wavelengths, i.e. 254 nm and 284 nm respectively. The chromatographic system consists of HiQSil C18HS column; an isocratic mobile phase consisted of methanol and tetrahydrofuran (95:5 v/v). The developed method is validated according to ICH guidelines in capsule dosage form. Validation of the developed method shows good result in range, linearity, accuracy and precision. Student’s t–test was used to correlate the two methods and applied to raw materials and capsule dosage form.